Autocuidado de diabetes: una mirada con perspectiva de género - Trujillo Olivera, Laura Elena; Nazar Beutelspacher, Austreberta (El Colegio de México A.C., 2011)
In Tuxtla Gutiérrez, Chiapas, a qualitative study was carried out, using a gender perspective to examine inter-gender relations in domestic groups and their influence on diabetics’ self-care. The empirical information was drawn from in-depth interviews with a number of patients and a person who was close to them. In this case, a self-care categorization is proposed based on what they say they do to control disease. The study revealed a significant inequality in the timeliness and achievements of self-care between the men and women suffering from this disease. The article explores the implications of women’s economic dependence, the consumption of alcoholic beverages, domestic violence, the sexual division of labor and the network of support for achieving self-care.